An Analysis of the Speaking Skill Development of English Education Students through Participation in English Debate Competitions - Yulianingsih; Amin, Muhammad; Junaidi, Ahmad; Elmiana, Dewi Satria (Program Studi Pendidikan Bahasa Inggris, 2025)
One of the most vital skills of English learning is speaking because it helps learners communicate and express ideas. The interactive and analytical nature of debate lets students practice using English as a tool of real-world communication as they build argumentation and reasoning skills. The purpose of the study is to discover what is enhanced in terms of speaking skills by taking part in debate competitions and to discuss how taking part in debate competitions enhances the speaking skills of English Education students at the University of Mataram. It was a qualitative cross-case study which used a sample size of five students who had one year of experience in competitive debate. The sources of data were semi-structured interviews and recording of debates (2023 and 2025). The recordings were processed with modified adaptation of the rubric on fluency, vocabulary, grammar, and cohesion created by Brown (2004), whereas the data of the interviews were processed with the interactive model developed by Miles et al. (2018). The results indicate that speaking proficiency of students significantly increased especially on fluency, vocabulary and cohesion, but grammatical improvements were minimal. The student stated that debate improved their speaking by giving them endless exposure to English, lots of practice, coach and peer feedback, active listening, and peer learning, which promoted the use of strategic language. To sum up, the idea of debate competition is useful to enhance fluency, confidence, and communicative competence of students; it is a useful tool to master speaking skills in EFL.